(3CfhGQ GdJfRjd hCSQGQ GdJChjds - (3GdHjVGhj, CHh SYjO, CHh GdNjQ, fGUQ GdOjf, YHO Gddg Hf YeQ Hf eMeO Hf Ydj(B685(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj fRd GdbQBf Ydi YHOg djchf ddYGdejf fPjQG hHYO aEf CYXe GdYdhe ebOGQG hCQaYgG TQaG hefGQG Yde GdJaSjQ ShQI GdaGJMI hJSei Ce GdbQBfs
(3BNQgG (B:s
(3ef bQC GdeYhPJjf acCfeG bQC GdcJH GdJj CfRdgG Gddg JYGdis
(3JHUQI GdYfhGf (B:s
(3JaSjQ GdHjVGhjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4/109s
(3cTa GdXfhf (B1/186s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs